2020
DOI: 10.1007/s10864-020-09375-5
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance and Generalization of Preschool Teachers’ Use of Behavior-Specific Praise Following In Situ Training

Abstract: This study tested the efficacy of in situ training via a multiple baseline design across participants for increasing four Head Start teachers' use of behavior specific praise (BSP) in classroom settings while evaluating concomitant changes in their classes' behavior. Of further interest was the extent to which Head Start teachers maintained and generalized use of BSP in untrained settings. The results of this study indicate that in situ training was effective for increasing Head Start teachers' use of BSP abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 76 publications
(190 reference statements)
0
2
0
Order By: Relevance
“…At the conclusion of each intervention session, the researcher informed the teacher of the number of BSP statements delivered and collected the Apple Watch. During this time, the researcher also provided retraining should a teacher fail to deliver at least 1 BSP statement per minute, a criterion utilized in previous research (LaBrot et al, 2020). Retraining consisted of a review of the potential impact of BSP on student behavior and a brief role-play of BSP use.…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the conclusion of each intervention session, the researcher informed the teacher of the number of BSP statements delivered and collected the Apple Watch. During this time, the researcher also provided retraining should a teacher fail to deliver at least 1 BSP statement per minute, a criterion utilized in previous research (LaBrot et al, 2020). Retraining consisted of a review of the potential impact of BSP on student behavior and a brief role-play of BSP use.…”
Section: Interventionmentioning
confidence: 99%
“…Following referral and consent to participate, a 20-min screening observation was conducted to verify low rates of teacher BSP. To be included in the study, a teacher must have demonstrated a praise rate lower than 0.5 BSP statements per minute-a previously utilized criterion (e.g., LaBrot et al, 2020). During screening observations, teachers were instructed to conduct their class in a typical manner and no supports were provided.…”
Section: Screeningmentioning
confidence: 99%